Umbilical Cord Mesenchymal Stem Cell Therapy for Regenerative Treatment of Rheumatoid Arthritis: Opportunities and Challenges - Lv X; Wang L; Zou X; Huang S (Dove Medical Press, 2021)
Xiaolan Lv,1,* Liming Wang,2,* XiaoRong Zou,3 Shigao Huang4 1Department of Laboratory Medicine, Liuzhou Maternity and Child Healthcare Hospital, Liu Zhou, Guang Xi, People's Republic of China; 2Shaanxi Jiuzhou Biomedical Science and Technology Group, Xi'an, Shaan Xi, People's Republic of China; 3Department of Hematology, 986 Hospital of Fourth Military Medical University, Xi'an, Shaan Xi, People's Republic of China; 4Faculty of Health Sciences, University of Macau, Macau, People's Republic of China*These authors contributed equally to this workCorrespondence: Shigao Huang Email huangshigao2010@aliyun.comAbstract: Rheumatoid arthritis (RA) is an autoimmune disease of unknown etiology with a high rate of disability. Traditional treatments for RA remain a challenging issue. For example, nonsteroidal anti-inflammatory drugs (NSAIDs) have no therapeutic effects on joint destruction, and the prominent side effects include gastrointestinal symptoms. RA is characterized by recurrence and bone attrition. Therefore, regenerative medicine and the use of umbilical cord mesenchymal stem cell (UC-MSC) therapies have recently emerged as potential options. UC-MSCs are multifunctional stem cells that are present in neonatal umbilical cord tissue and can differentiate into many kinds of cells, which have broad clinical application prospects in the tissue engineering of bone, cartilage, muscle, tendon, ligament, nerve, liver, endothelium, and myocardium. Moreover, UC-MSCs have advantages, such as convenient collection of materials and no ethical disputes; thus, these cells have attracted increasing attention from researchers. However, there are few clinical studies regarding UC-MSC therapy for RA. In this paper, we will review traditional drugs for RA treatment and then focus on UC-MSC therapy for RA, including preclinical and clinical UC-MSC applications for RA patients in the context of regenerative medicine. Finally, we will summarize the challenges and perspectives of UC-MSCs as a potential therapeutic strategy for RA. This review will help to design and discover more potent and efficacious treatments for RA patients and aid in advancing this class of cell therapy.Keywords: cell-based therapies, rheumatoid arthritis, mesenchymal stem cells, umbilical cord, regenerative medicine